ANALISIS YURIDIS PERTIMBANGAN HAKIM DALAM TINDAK PIDANA PENGANIAYAAN YANG MENYEBABKAN KEMATIAN DITINJAU DARI PASAL 50 AYAT (1) UU KEKUASAAN KEHAKIMAN (Studi Kasus Putusan 454/Pid.B/2024/PN Sby) - NIM. A1011211223, AGIE NOVELINA SIMANJUNTAK (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This research is motivated by the inconsistency between the facts revealed in court and the judicial decision in the case of assault resulting in death in Decision Number 454/Pid.B/2024/PN Sby. The main issue addressed is the juridical analysis of the judge